Application of Coagulants for Humic Acid and Algae Removal in Micro-Polluted Source Water Treatment - Zheng1, Huaili; Xie1, Wanying; Zhao1, Chun; Guo1, Jingsong; Tang1, Xiaomin; Chen1, Wei; Liang1, Jianjun; Tshukudu2, Tiroyaone (Asian Journal of Chemistry, 2014)
The source water has much relationship to human health, which also plays an indispensable role of our daily life. The pollutions of micro-polluted source water, which contain alga and humic substances have become one serious environmental issue. How to converse environmental pollution and treat micro-polluted source water efficiently is in urgency. That some cost-effective coagulants which as one avenue to remove alga and humic substances were summarized in this paper. The coagulation performance and effect mechanism were also summarized.